Degradation of pesticide residue in 'Mahajanaka' mango fruit during storage at different conditions - W. Pattanapo (2018)
The degradation of pesticide in mango 'Mahajanaka' from Wiang Nong Long district, Lumphun province, was studied. Profenofos and carbaryl residue of mango fruits was measured after dip in profenofos + carbaryl in 500 and 850 mg L-1, respectively. The results found that at 25°C profenofos degraded faster than at 5 and 13°C. The concentrations of profenofos were 0.23, 0.29 and 0.46 mg kg-1 after dip in pesticide at 6, 15 and 18 days, respectively. The carbaryl residue was non-detectable in the mango stored at 13 and 25°C for 3 days, while in the stored mango in 5°C, 0.13 mg kg-1 of the residue was still detected, which is lower than the MRL of Thai Agricultural Standard, established by the National Bureau of Agricultural Commodity and Food Standards.